Interfacial fracture of dentin adhesively bonded to quartz-fiber reinforced composite - Melo, Renata M. [UNESP]; Rahbar, Nima; Soboyejo, Wole (Elsevier B.V., 2011)
The paper presents the results of an experimental study of interfacial failure in a multilayered structure consisting of a dentin/resin cement/quartz-fiber reinforced composite (FRC). Slices of dentin close to the pulp chamber were sandwiched by two half-circle discs made of a quartz-fiber reinforced composite, bonded with bonding agent (All-bond 2, BISCO, Schaumburg) and resin cement (Duo-link. BISCO, Schaumburg) to make Brazil-nut sandwich specimens for interfacial toughness testing. Interfacial fracture toughness (strain energy release rate, G) was measured as a function of mode mixity by changing loading angles from 0 degrees to 15 degrees. The interfacial fracture surfaces were then examined using Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray Spectroscopy (EDX) to determine the failure modes when loading angles changed. A computational model was also developed to calculate the driving forces, stress intensity factors and mode mixities. Interfacial toughness increased from approximate to 1.5 to 3.2 J/m(2) when the loading angle increases from approximate to 0, 0 to 15 degrees. The hybridized dentin/cement interface appeared to be tougher than the resin cement/quartz-fiber reinforced epoxy. The Brazil-nut sandwich specimen was a suitable method to investigate the mechanical integrity of dentin/cement/FRC interfaces. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Interfacial fracture toughness; Resin cements; Dentin bonding agents; Fiber reinforced composite